2013
DOI: 10.1016/j.rmed.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic significance of coagulation assays in lung cancer

Abstract: Activation of coagulation and fibrinolysis is frequently encountered among cancer patients. Such tumors are supposed to be associated with higher risk of invasion, metastases and eventually worse outcome. The aim of this study is to explore the prognostic value of blood coagulation tests for lung cancer patients. The study comprised 110 lung cancer patients. Pretreatment blood coagulation tests including PT, aPTT, PTA, INR, D-dimer, fibrinogen levels and platelet counts were evaluated. The plasma level of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
66
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 33 publications
15
66
1
Order By: Relevance
“…Additionally, significant differences in the plasma levels of LDH, CEA, D-dimer, VWF and ADAMTS-13, and FVIII activity were observed between patients with and without distant metastasis. These results are in agreement with those of previous studies, which demonstrated an increased tendency for the development of coagulative and fibrinolytic disorders in patients with metastatic diseases (3,21). Furthermore, these results are similar to the observations of Oleksowicz et al (22), who identified increased VWF levels and ADAMTS-13 deficiencies in patients with metastatic tumors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, significant differences in the plasma levels of LDH, CEA, D-dimer, VWF and ADAMTS-13, and FVIII activity were observed between patients with and without distant metastasis. These results are in agreement with those of previous studies, which demonstrated an increased tendency for the development of coagulative and fibrinolytic disorders in patients with metastatic diseases (3,21). Furthermore, these results are similar to the observations of Oleksowicz et al (22), who identified increased VWF levels and ADAMTS-13 deficiencies in patients with metastatic tumors.…”
Section: Discussionsupporting
confidence: 93%
“…Significant increases in the blood concentrations of thrombin-antithrombin III complexes, fibrinogen and D-dimer have been reported in patients with lung cancer exhibiting extensive or limited disease. The extent of such activation of these markers has also been associated with tumor stage and prognosis (2,3). However, the origin of the activation of the coagulative-fibrinolytic system in lung cancer remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a growing body of evidence suggests the existence of a correlation between activation of coagulation and fibrinolysis and tumor angiogenesis, invasion, progression, and metastatic spread [9][10][11][12][13][14][15][16]. In clinical studies, many researchers have documented the relationship between hemostatic abnormalities and several malignancies, and various hemostasis markers associated with tumor staging and prognosis have previously been reported [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In lung cancer, plasma fibrinogen and D-dimer levels are associated with tumor pathological stage, response to therapy, and survival [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies, many researchers have documented the relationship between hemostatic abnormalities and several malignancies, and various hemostasis markers associated with tumor staging and prognosis have previously been reported [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In lung cancer, plasma fibrinogen and D-dimer levels are associated with tumor pathological stage, response to therapy, and survival [26][27][28][29][30]. However, only a few patients with SCLC were included in these studies [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation